2007
DOI: 10.14411/eje.2007.090
|View full text |Cite
|
Sign up to set email alerts
|

Mating periodicity and post-mating refractory period in the zoophytophagous plant bug Macrolophus caliginosus (Heteroptera: Miridae)

Abstract: Abstract. The zoophytophagous mirid bug Macrolophus caliginosus is an important biocontrol agent of whiteflies in the Mediterranean region. Periods of low productivity in commercial breeding units and unsuccessful establishment in greenhouses prompted this study of mating behaviour. Here we describe copulation behaviour, the diel mating periodicity and post-copulatory refractory period. A natural plant substrate needs to be provided if one wants to observe the copulatory behaviour of M. caliginosus in the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…This result, however, does not prove that females are never attracted to males. The insects used in this study were Þeld collected and a large proportion may have mated before the bioassays, decreasing their sexual responsiveness to males as is the case for a wide range of insects, including hemipterans such as the rice leaf bug, Trigonotylus caelestialium (Kirkaldy) (Yamane et al 2011), and the whiteßy predator, Macrolophus caliginosus Wagner (Gemeno et al 2007). There remains the possibility that unmated females would be attracted to male bugs.…”
Section: Discussionmentioning
confidence: 99%
“…This result, however, does not prove that females are never attracted to males. The insects used in this study were Þeld collected and a large proportion may have mated before the bioassays, decreasing their sexual responsiveness to males as is the case for a wide range of insects, including hemipterans such as the rice leaf bug, Trigonotylus caelestialium (Kirkaldy) (Yamane et al 2011), and the whiteßy predator, Macrolophus caliginosus Wagner (Gemeno et al 2007). There remains the possibility that unmated females would be attracted to male bugs.…”
Section: Discussionmentioning
confidence: 99%
“…Most mirids become sexually mature several days after adult emergence, and female mirids could release volatile sex pheromones to attract conspeciÞc males (Zhang and Aldrich 2003, Innocenzi et al 2005, Gemeno et al 2007). In our study, males of A. suturalis responded to odors from sexually mature virgin female in a Y-tube bioassay, indicating that mature females could attract males.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because the female production of pheromone is maximal during this time, and another reason may be that females produce pheromone all the time, but males only respond during this time. Similar results have been reported in previous studies, males of P. difficilis ßight to sex-attractant traps started Ϸ1800 hours and stopped after midnight, with peak ßight occurring between 2000 and 2200 hours, and no ßights to the traps were observed during daytime (Zhang and Aldrich 2003); in P. calli, males were collected or trapped during the Þrst half of the scotophase (after sunset to midnight) (Zhang and Aldrich 2008); and in Macrolophus caliginosus, mating was most frequent in the scotophase and the Þrst half of the photophase (Groot et al 1998, Gemeno et al 2007). However, females of S. rubrovittatus could be attractive to males in a broad time of day except from 1200 to 1600 hours when baited with 10 virgin females per trap (Kichishima et al 2009), and no daily periodicity was found in sex pheromone emission by females in T. caelestialium (Higuchi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The plant bug, Adelphocoris suturalis Jakovlev is now a major pest on cotton in Southern China (Lu et al, 2008a). Mirid pheromones serve as the key mediators of intra-or-inter-specific communications, one of this is that a female produces volatile sex pheromones to attract conspecific male to copulation (Gemeno et al, 2007;Innocenzi et al, 2005). Our previous work reported that a female becomes sexually mature 4 days after adult emergence and they produced sex pheromones around 8-11 days old (Zhang et al, 2011), these pheromones are synthesized and released by metathoracic scent glands (MTGs) which are composed of well-developed reservoir and paired lateral glands (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%